Impact of Storm-Enhanced Density (SED) on Ion Upflow Fluxes During Geomagnetic Storm - Zou, Shasha; Ren, Jiaen; Wang, Zihan; Sun, Hu; Chen, Yang (Frontiers in Astronomy and Space Sciences, 2021)
The impact of the dynamic evolution of the Storm-Enhanced Density (SED) on the upward ion fluxes during the March 06, 2016 geomagnetic storm is studied using comprehensive multi-scale datasets. This storm was powered by a Corotating Interaction Region (CIR), and the minimum Sym-H reached ~-110 nT. During the ionospheric positive storm phase, the SED formed and the associated plume and polar cap patches occasionally drifted anti-sunward across the polar cap. When these high-density structures encountered positive vertical flows, large ion upward fluxes were produced, with the largest upward flux reaching 3 x 1014 m-2s-1. These upflows were either the type-1 ion upflow associated with fast flow channels, such as the sub-auroral polarization stream (SAPS) channel, or the type-2 ion upflow due to soft particle precipitations in the cusp region. The total SED-associated upflow flux in the dayside cusp can be comparable to the total upflow flux in the nightside auroral zone despite the much smaller cusp area compared with the auroral zone. During the ionospheric negative storm phase, the ionospheric densities within the SED and plume decreased significantly and thus led to largely reduced upward fluxes. This event analysis demonstrates the critical role of the ionospheric high-density structures in creating large ion upward fluxes. It also suggests that the dynamic processes in the coupled ionosphere-thermosphere system and the resulting state of the ionospheric storm are crucial for understanding the temporal and spatial variations of ion upflow fluxes and thus should be incorporated into coupled geospace models for improving our holistic understanding of the role of ionospheric plasma in the geospace system.